A randomised, placebo-controlled, phase III trial of leniolisib in activated phosphoinositide 3-kinase delta (PI3Kδ) syndrome (APDS): Adolescent and adult subgroup analysis - Rao, V Koneti; Šedivá, Anna; Dalm, Virgil A S H; Plebani, Alessandro; Schuetz, Catharina; Shcherbina, Anna; Trizzino, Antonino; Zharankova, Yulia; Orpia, Alanvin; Kulm, Elaine; Webster, Sharon; Körholz, Julia; et al. (Clinical immunology, 2025)
Activated phosphoinositide 3-kinase delta (PI3Kδ) syndrome (APDS) is an ultra-rare, progressive genetic disease, characterised by immune deficiency and dysregulation, affecting individuals from birth. In a 12-week phase III randomised placebo-controlled trial, leniolisib, a selective PI3Kδ inhibitor, was well-tolerated and met both co-primary endpoints (change from Baseline in log10-transformed sum of product of diameters of index lymph nodes and percentage of naïve/total B cells at Day 85). Here, prespecified subgroup analyses are reported in adolescents aged 12-17 years (leniolisib, n = 8; placebo, n = 4) and adults aged ≥18 (leniolisib, n = 13; placebo, n = 6). In both subgroups, leniolisib reduced lymphadenopathy (least squares mean change versus placebo: adolescents, -0.4 versus -0.1; adults, -0.3 versus 0.1) and increased the percentage of naïve B cells (least squares mean change: adolescents, 44.5 versus -16.5; adults, 28.4 versus -1.1). Leniolisib was well-tolerated in both adolescents and adults. These results show leniolisib is an effective APDS treatment in both subpopulations. PLAIN LANGUAGE SUMMARY: What is activated PI3Kδ syndrome (APDS)? APDS is an ultra-rare disease in which the immune system does not work correctly. People with APDS have a wide range of symptoms, including infections, certain organs associated with the immune system becoming larger, and worse quality of life. These symptoms generally start in childhood. Why was this study carried out? Current treatments only treat the symptoms of APDS, rather than correcting the cause of the problem. These treatments can also have significant side effects. A new medication for APDS called leniolisib aims to treat the underlying cause of the disease. This publication reports results from a clinical trial of leniolisib which compared patients who received leniolisib with patients who received a placebo. The aim of this report was to examine these clinical trial results to understand if leniolisib is effective and safe when treating both adolescents (12-17 years old) and adults (18 years and older) with APDS. What were the results of this study? Leniolisib improved the number of certain immune cells, compared to patients who did not receive leniolisib, in both adolescents and adults with APDS. Leniolisib also reduced the size of the enlarged immune system organs in both adolescents and adults with APDS. There were no major safety concerns for either age group who received leniolisib. What do these results mean? These results show that leniolisib can help the immune system to work in a way that is closer to those without APDS. This new treatment is effective and generally well-tolerated for both adolescents and adults. These results indicate that people with APDS are able to start treatment with leniolisib during adolescence, which may slow the build-up of symptoms and may also have a positive impact on the quality of their lives.
Keywords: dospělí; Double-Blind Method; primární imunodeficience; Humans; lidé středního věku; Middle Aged; mladý dospělý; mužské pohlaví; B-Lymphocytes; Adult; Adolescent; Primary Immunodeficiency Diseases; ženské pohlaví; B-lymfocyty; lidé; mladiství; dítě; Child; fosfatidylinositol-3-kinasy třídy I; Male; Young Adult; Class I Phosphatidylinositol 3-Kinases; dvojitá slepá metoda; Female